Honor's voice : the transformation of Abraham Lincoln - Wilson, Doug (Douglas L.) (New York : Alfred A. Knopf : Distributed by Random House, 1998)
Examines certain aspects of the life of Abraham Lincoln in the years between 1831 and 1842, presenting him as a stubborn youth, partial to off-color jokes, and prone to depression; and traces the process by which he rose from unskilled laborer to a position of prominence in the Illinois legislature
Includes bibliographical references (p. [325]-370) and index
Keywords: Lincoln, Abraham, -- 1809-1865 -- Political career before 1861.; Presidents -- United States -- Biography; Illinois -- Politics and government -- To 1865.